2022
DOI: 10.3390/ijerph191911902
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-19-Related Restrictions on the Prevalence of Overweight and Obese Czech Children

Abstract: Apart from influencing the health of the worldwide population, the COVID-19 pandemic changed the day-to-day life of all, including children. A sedentary lifestyle along with the transformation of eating and sleep habits took place in the child population. These changes created a highly obesogenic environment. Our aim was to evaluate the current weight in the child population and identify the real effects of the pandemic. Height and weight data were collected by pediatricians from the pre-COVID-19 and post-COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Quality was assessed using the modified Newcastle–Ottawa Scale [ 19 ]. Out of included forty studies, 16 were classified as good quality [ 26 , 27 , 33 38 , 45 , 46 , 48 , 49 , 54 , 58 , 59 ] while twenty-four were also classified as satisfied [ 21 25 , 28 31 , 39 44 , 47 , 50 53 , 55 – 57 , 60 ]. Twenty-four articles were done on the adult population [ 22 , 23 , 25 , 26 , 28 30 , 36 , 38 , 42 44 , 46 , 48 50 , 55 , 57 59 ], five articles were done only adolescents [ 31 , 39 , 41 , 47 , 60 ], three research articles were also done on children [ 34 , 53 , 54 ], and finally, eight articles were done on both children and adolescents [ 21 , 24 , 27 , 33 , 37 , 45 , 52 , 56 ] as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality was assessed using the modified Newcastle–Ottawa Scale [ 19 ]. Out of included forty studies, 16 were classified as good quality [ 26 , 27 , 33 38 , 45 , 46 , 48 , 49 , 54 , 58 , 59 ] while twenty-four were also classified as satisfied [ 21 25 , 28 31 , 39 44 , 47 , 50 53 , 55 – 57 , 60 ]. Twenty-four articles were done on the adult population [ 22 , 23 , 25 , 26 , 28 30 , 36 , 38 , 42 44 , 46 , 48 50 , 55 , 57 59 ], five articles were done only adolescents [ 31 , 39 , 41 , 47 , 60 ], three research articles were also done on children [ 34 , 53 , 54 ], and finally, eight articles were done on both children and adolescents [ 21 , 24 , 27 , 33 , 37 , 45 , 52 , 56 ] as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The current study identified that age which is a biological determinant was found to be one of the risk factors for obesity/ weight gain during the COVID-19 pandemic lockdown. Twelve studies identified age as a significant contributing factor to obesity/weight gain [ 21 , 27 , 33 , 35 , 37 , 39 , 43 , 48 , 49 , 51 , 52 , 54 ]. The minimum mean age group reported ranged from mean 10.8 (SD = 0.46) [ 20 ] and the maximum mean age group reported was 47.9 (SD = 16) [ 36 ].…”
Section: Age Of Participantsmentioning
confidence: 99%
“…There have been numerous recent reports about childhood obesity rates during the COVID period. These reports have used various methods and have originated from various locations [ 7 , 8 , 10 , 13 , 14 , 17 ]. Two related reports about children treated in Kaiser Permanente of Southern California found increasing rates of overweight and obesity in that population during the COVID period.…”
Section: Discussionmentioning
confidence: 99%
“…While full school closures occurred in almost all European countries, this was not the case in Sweden and Iceland and the length of closures varied significantly (see Figure 1.12 below). Source and age groups (for young people): France: Santé publique France (2022 [4]), https://www.santepubliquefrance.fr/etudes-et-enquetes/coviprev-uneenquete-pour-suivre-l-evolution-des-comportements-et-de-la-sante-mentale-pendant-l-epidemie-de-covid-19 (18)(19)(20)(21)(22)(23)(24); Belgium: Sciensano (2022 [6]) https://datastudio.google.com/embed/reporting/7e11980c-3350-4ee3-8291-3065cc4e90c2/page/ykUGC (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29); Denmark, Estonia, Iceland, Sweden and Norway: Unnarsdóttir et al (2021 [7]) (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29); https://doi.org/10.1093/ije/dyab234; United Kingdom (Great Britain): Office for National Statistics (2021 [13]), https://www.ons.gov.uk/peoplepopulationandcommunity/wellbeing/datasets/coronavirusanddepressioninadultsingreatbritain (16)(17)(18)(19)(20)(21)(22)(23)…”
Section: Figure 11 Symptoms Of Depression Amongst Young People More T...mentioning
confidence: 99%
“…The State of Vaccine Confidence in the EU 2020 survey showed that the share of respondents who strongly agreed that seasonal influenza vaccination was important rose by nearly 10 percentage points on average across EU countries between 2018 and 2020, and by over 10 percentage points for those who strongly agreed that seasonal influenza vaccination was safe. Overall, more than three-quarters (77%) of respondents considered that influenza vaccination was important and 80% that it was safe (Figueiredo et al, 2020 [7]).…”
Section: The Pandemic Has Helped To Increase Vaccination Uptake For I...mentioning
confidence: 99%